Decreased ratio of influenza-specific IgG versus IgM in response to influenza vaccination in antiretroviral-treated HIV-infected African Americans compared to Caucasians, and its direct correlation with the percentages of peripheral Tfh cells. Issue 8 (18th February 2020) - Ma, Ping; Luo, Zhenwu; Qian, Jing; Yan, Zhongfang; Zhang, Lumin; Martin, Lisa; Wang, Ziyu; Xia, Huan; Yu, Fangfang; Jiang, Wei
Abstract: Background: Racial differences have been observed in the rate of bacterial infection and disease progression in HIV. Here, we evaluate racial differences in seasonal influenza vaccine responses. Methods: 16 healthy controls (9 Caucasians (CC) and 7 African Americans (AA)) and 26 antiretroviral therapy (ART)-treated aviremic HIV+ subjects (11 CC and 15 AA) were enrolled in the current study. Blood was collected at pre-vaccination (D0) and day 14 (D14) following seasonal influenza vaccination. Serologic responses were characterized in plasma by ELISA. B and T cells were assessed by flow cytometry ex vivo . Results: The absolute counts of CD4+ CD3+ T cells and CD19+ B cells were similar in healthy controls and HIV-infected individuals, and similar in CC and AA in the two study groups. However, the percentage of peripheral T follicular helper (pTfh) cells was decreased in HIV+ AA compared to HIV+ CC. There were no racial differences in IgG antibody responses against vaccination in the two study groups. However, the ratio of anti-influenza-specific IgG versus IgM induction following vaccination was decreased in HIV+ AA compared to HIV+ CC, which was directly correlated with the percentages of pTfh cells. This racial difference and correlation were not demonstrable in healthy controls. Conclusion: Here we report that HIV + AA has decreased fold induction of IgG versus IgM after influenza vaccination, which may suggest impaired class-switching from IgM to IgG in AA HIV-infected individuals.